2007
DOI: 10.1007/s11126-007-9055-x
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant Treatment and Adherence to Combination Antiretroviral Therapy among Patients with AIDS and Diagnosed Depression

Abstract: Background-The prevalence of depression is elevated among HIV-infected individuals and there is evidence that depression exerts a negative impact on HIV medication adherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(38 citation statements)
references
References 42 publications
2
35
1
Order By: Relevance
“…The current literature on adherence notes that clinicians should implement appropriate interventions to improve adherence. For example, use of antidepressants also improved adherence among depressed HIV infected individuals [18,19]. Similarly, Methadone Maintenance Treatment improved adherence among HIV infected individuals [28].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The current literature on adherence notes that clinicians should implement appropriate interventions to improve adherence. For example, use of antidepressants also improved adherence among depressed HIV infected individuals [18,19]. Similarly, Methadone Maintenance Treatment improved adherence among HIV infected individuals [28].…”
Section: Discussionmentioning
confidence: 97%
“…Further, the treatment of depression improves cognitive functioning [9,10]. A number of studies found a positive effect of antidepressants on the adherence of HIV medication [17][18][19]. However, none of the studies examined the variation in the effect of antidepressant use with medication complexity on medication adherence among depressed individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Mental illness among individuals with HIV has been associated with negative outcomes including decreased quality of life, 4,[6][7][8] AIDS-related morbidity and mortality, 9,10 delayed entry into medical care, 5,11,12 poorer medication adherence, 4,8,[13][14][15] risky sexual and drug use behaviors 12,16 and substantial costs including productivity loss and health care expenditures. 10,17,18 Mental health treatment, including mental health counseling and psychopharmacologic treatment, has been associated with improvements in mental health functioning [19][20][21][22][23][24][25][26] as well as greater HIV-related medication use and adherence 10,19,[27][28][29][30][31] and higher CD4 counts. 24,32 Although some studies have found psychopharmacologic treatment to have benefit in improving psychiatric symptoms and medication use, 27,31,32 one study found no association of psychopharmacologic treatment alone on HIV medication use.…”
Section: Introductionmentioning
confidence: 99%
“…10,17,18 Mental health treatment, including mental health counseling and psychopharmacologic treatment, has been associated with improvements in mental health functioning [19][20][21][22][23][24][25][26] as well as greater HIV-related medication use and adherence 10,19,[27][28][29][30][31] and higher CD4 counts. 24,32 Although some studies have found psychopharmacologic treatment to have benefit in improving psychiatric symptoms and medication use, 27,31,32 one study found no association of psychopharmacologic treatment alone on HIV medication use. 29 This study found that mental health counseling alone or in conjunction with psychopharmacologic treatment was associated with greater HIV medication utilization.…”
Section: Introductionmentioning
confidence: 99%
“…2,[27][28][29][30] Several reports indicate that cellular immune responses in women may be altered with depression. 29 Fortunately, treatment of depression pharmacologically or through other behavioral interventions can be beneficial with demonstrated improved clinical outcomes and HAART adherence; 12,[31][32][33][34][35][36] however, differential use of antidepressants has been documented. [37][38][39] The relationship of depression and its treatment and HAART adherence is a dynamic one and longitudinal evaluations of HIV-infected persons in the evolving chronic disease model of care are needed.…”
mentioning
confidence: 99%